Physiological and Yield Responses of Spring Wheat Cultivars under Realistic and Acute Levels of Ozone - Nivedita Chaudhary (MDPI AG, 2021)
Tropospheric ozone (O3) is widely recognized as the cause of substantial yield and quality reduction in crops. Most of the previous studies focused on the exposure of wheat cultivars to elevated O3 levels. Our main objectives were to: (i) investigate the consistency of wheat cultivars’ physiological responses across two different realistic O3 levels; and (ii) compare these physiological responses with those under short acute O3 exposure. Three commercially available hard spring wheat cultivars bred under semiarid and Eastern Mediterranean conditions were exposed to two different O3 levels during two consecutive seasons (2016–2018)—36 and 71 ppbv 7 h mean O3 mixing ratios in open-top chambers. The results were compared to those following short acute O3 exposure (102.8 ppbv, 7 h mean for 10 days) in a greenhouse. Non-stomatal responses were significantly more pronounced than stomatal responses in all cultivars under different levels of O3. The specific cultivar was observed as the most O3-tolerant under all experiments. The fact that the same cultivar was found remarkably tolerant to the local semiarid ambient conditions according to other studies and to O3 exposure based on the present study supports a link between cultivar resistance to drought conditions and O3.